Go your own way - Andrus, Joel L.; Withers, Michael C.; Courtright, Stephen H.; Boivie, Steven (Strategic Management Journal, 2019)
[Research Summary: Why do top executives leave their firms? Research on executive turnover has either focused on CEO dismissal or on group-level top management team (TMT) departure rates, mostly ignoring individual-level factors that would predict why non-CEO executives exit. Here, we extend the shock perspective of the unfolding model of turnover used in organizational behavior research to show how relational and reputational shocks influence turnover at the executive level. Our sample includes over 4,000 executives from S&P 1500 firms over 11 years. We hypothesize and find that relational and reputational shocks increase the likelihood of top executive exit. We also consider the moderating influence of pay disparity on these relationships, which impacts how each type of shock influences executive turnover. Managerial Summary: Replacing top executives can be extremely costly for firms. Consequently, understanding the reasons behind top executive exit are important. We examine the effect of different types of shock on the likelihood a top executive will exit their firm. We find that both relational shocks (e.g., other members of the TMT leaving), as well as reputational shocks (e.g., litigation or shareholder activism against the firm), increase turnover. However, we find that higher status executives experience these shocks differently than lower status executives.]